Analysis Of Risk Factors For Acute Kidney Injury (AKI) With The Use Of Favipiravir And Remdesivir In Covid-19 Patients At Fatmawati Central General Hospital - Nurlela Nurlela; Hesty Utami Ramadaniati; Yusi Anggriani; Ahmad Subhan (SEAN Institute, 2024)
COVID-19 patients are very vulnerable to complications of Acute Kidney Injury (AKI), there are many factors causing complications one of which is kidney toxic therapy, antiviral therapy is considered potentially toxic to the kidneys because most of it is excreted through the kidneys. This study was conducted to examine the risk factor profile of AKI in COVID-19 patients taking antivirals Remdesivir and Favipiravir. This study is an observational study with a cross-sectional design at Fatmawati Hospital. The sampling method uses total sampling during the period August 2020-July 2021. The data used is medical record. Bivariate analysis uses Chi-square, and multivariate analysis uses logistic regression. a sample of 208 patients who met the inclusion criteria in the period August 2020-July 2021 in the COVID-19 isolation room of Fatmawati Hospital. 135 patients using Favipiravir, 37 identified as having an AKI event and 73 patients using Remdesivir, 19 were identified as having an AKI event. Multivariate analysis with logistic regression showed that male sex and severity of severe to critical severity significantly influenced the incidence of AKI. The use of Favipiravir and Remdesivir in COVID-19 patients is not a risk factor for AKI.